The effect of pathogenesis-related 10 (Pr-10) gene on the progression of fusarium wilt in Musa acuminata cv. Berangan - Baharum, Nadiya Akmal; Othman, Rofina Yasmin; Mohd Yusuf, Yusmin; tan, Boon Chin; Zaidi, Kamilatulhusna; Khalid, Norzulaani (Penerbit UKM, 2018)
PR-10 is a member of pathogenesis-related (PR) genes elicited by the plant’s defense mechanism during pathogen attack. Elevated expression of PR-10 upon different pathogen invasions has been observed in many plant species suggesting its role as an anti-bacterial, anti-viral and anti-fungal gene. However, the effect of PR-10 in mitigating the infection of Fusarium oxysporum f. sp. cubense (Foc), the causal agent of Fusarium wilt in banana has not been reported. In this study, the coding sequences of PR-10 gene isolated from Foc resistant Musa acuminata ssp. malaccensis (MaPR-10) were integrated into a local Foc susceptible commercial banana cultivar, Berangan via co-cultivation of embryogenic cell suspension and Agrobacterium tumefaciens. Out of 17 putative transgenic lines established, 11 of them positively harbored MaPR-10. Among these, Line-19 plantlets showed the most rapid in-vitro propagation and successfully over- expressed the transgene. Following a nursery challenge experiment with a virulent Foc race 4 (CI HIR) isolate, about 30% of Line-19 plants showed a one-week delay in disease progression when compared to the untransformed controls. From the final evaluation performed in the 5th week-post-inoculation, the leaf symptoms index (LSI) and rhizome discoloration index (RDI) of Line-19 was 3.4 and 6.1, respectively, indicating the disease had progressed. The findings of this study enrich the current existing knowledge on the roles of PR-10 in combating fungal disease in plants.